MEMS electrochemical gas sensor and processing method thereof

By adopting semi-solid electrolyte layer and MEMS process in MEMS electrochemical gas sensor, combined with the microstructure design of breathable substrate structure and working electrode, the problem of insufficient response signal in miniaturization of MEMS electrochemical gas sensor is solved, and efficient and economical gas monitoring is achieved.

CN119666941APending Publication Date: 2025-03-21ZHENGZHOU WINSEN ELECTRONICS TECH CO LTD

Patent Information

Application Number
CN202411753521.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing MEMS electrochemical gas sensors are difficult to miniaturize while keeping the sensor response signal large enough.

Method used

A MEMS electrochemical gas sensor is designed using a semi-solid electrolyte layer and combined with a MEMS process. The sensor consists of a breathable substrate structure, counter electrode, semi-solid electrolyte layer and working electrode. The semi-solid electrolyte layer is formed by spraying or spin coating. After drying and curing, a thin film structure with high conductivity and high mechanical strength is formed. The surface of the working electrode is roughened and a concave and concave structure is provided at the interface between the semi-solid electrolyte layer and the working electrode to increase the effective contact area.

Benefits of technology

It realizes the high response signal in the miniaturized sensor, the load resistance is 1,000 ohms and the output current is μA, and it can effectively monitor gases such as carbon monoxide, ethanol, and formaldehyde. The sensor is simple in structure and is suitable for mass production and integrated packaging, which significantly reduces the cost per sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666941A_ABST
    Figure CN119666941A_ABST
Patent Text Reader

Abstract

The invention provides an MEMS electrochemical gas sensor and a processing method thereof. The sensor is mainly composed of a breathable substrate structure, a counter electrode, a semi-solid electrolyte layer and a working electrode, the counter electrode, the semi-solid electrolyte layer and the working electrode form a sandwich structure, the thickness of the semi-solid electrolyte layer is 1-30 microns, and the semi-solid electrolyte layer is mainly of a film structure formed by baking a semi-solid electrolyte solution. According to the MEMS electrochemical gas sensor, the semi-solid electrolyte layer is mainly processed based on a semi-solid electrolyte material by adopting processes such as spraying or spin-coating, drying and curing, and the MEMS electrochemical gas sensor is designed and prepared by combining an MEMS process, so that the size of the sensor structure can be 1 mm, the miniaturized and zero-power-consumption work is realized, the gas sensor has a good response signal, and the gas sensor has a good application prospect. The load resistance is in a kiloohm level, and the output current is in a [mu] A level. The sensor can be used for monitoring reducing gases such as carbon monoxide, ethanol, formaldehyde and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sensor technology, and in particular to a MEMS electrochemical gas sensor and a processing method thereof. Background Art

[0002] Fuel cell-type electrochemical gas sensors have the advantages of accuracy, reliability, zero power consumption, and high sensitivity. However, electrochemical sensors produced by traditional assembly methods are large in size and difficult to integrate into terminal applications such as mobile phones. In addition, large-scale production requires a lot of labor.

[0003] The patent application (application number CN 202311116378.3) discloses a membrane electrode for a gas sensor, its preparation method and application. In the patent application, a sheet-like solid Nafion electrolyte membrane is used. After preparing the electrode slurry, the working electrode and the counter electrode are processed on the surface of both sides of the electrolyte membrane by hot pressing or printing, and then the production of the electrochemical sensor is completed by assembly. The patent application (application number CN 202311250266.7) discloses a method for preparing a PCB-based electrochemical semi-solid gas sensor. In the patent application, a semi-solid organic gel electrolyte is used, and the Nafion solution is only used as a proton conductive layer to cover and connect the coplanar electrodes. However, the above-mentioned electrochemical sensor is not based on MEMS technology, the structure volume is large, and it is impossible to achieve miniaturization and integration.

[0004] MEMS technology can significantly reduce the size of sensors and realize the simultaneous processing and production of multiple sensors on a substrate, thereby reducing the cost of each sensor. In order to achieve miniaturization, the sheet electrolyte materials used in traditional electrochemical sensors are not applicable because they need to be cut and assembled for use, which is incompatible with MEMS technology; liquid electrolytes are also difficult to make into miniaturized structures because of the difficulty of injecting liquids and sealing. Currently used solid electrolyte materials, such as lithium phosphate, can be formed into films through thermal evaporation processes, but there are two problems with this type of material: ① It can only work when heated to hundreds of degrees and has no ionic conductivity at room temperature. Once heated to work, an external voltage is required, that is, zero power consumption cannot be achieved; ② Even if it is heated to make it work, the output signal is very low because the ionic conductivity of solid electrolyte materials is generally relatively low (liquid).

[0005] The patent application (application number CN 202110866623.7) discloses an ultra-thin all-solid-state formaldehyde electrochemical gas sensor. The patent application uses Nafion solution as one of the components of the electrolyte slurry, but the solid electrolyte membrane layer made therefrom is tens to hundreds of microns thick, and a catalytic layer needs to be covered between each electrode and the electrolyte to work. The patent application (application number CN 202410012524.6 discloses a hybrid potential gas sensor based on MEMS technology and a preparation method thereof. Although the patent application uses MEMS processing technology, no special process treatment is performed on the substrate, electrodes, etc., so the sensor response signal produced will be very low.

[0006] Therefore, it is difficult for existing MEMS electrochemical gas sensors to achieve miniaturization while ensuring that the sensor response signal is large enough. Summary of the invention

[0007] In view of this, the main purpose of the present invention is to use a semi-solid electrolyte in combination with MEMS technology to propose a MEMS electrochemical gas sensor and a processing method thereof, so as to achieve miniaturization while ensuring that the sensor response signal is large enough.

[0008] Specifically, the technical solution protected by the present invention is as follows: A MEMS electrochemical gas sensor mainly consists of a gas permeable substrate structure, a counter electrode, a semi-solid electrolyte layer and a working electrode, wherein the counter electrode is arranged on the gas permeable substrate structure, and the counter electrode, the semi-solid electrolyte and the working electrode form a "sandwich" structure, wherein the semi-solid electrolyte layer is mainly a thin film structure formed by baking a semi-solid electrolyte solution. The semi-solid electrolyte solution is mainly an electrolyte composed of a solid polymer and a liquid plasticizer, and the semi-solid electrolyte layer formed by baking has high conductivity, high mechanical strength and good high temperature stability. The thickness of the semi-solid electrolyte layer is preferably 1-30 μm.

[0009] In order to improve the sensor response signal and make the working electrode fully contact with the gas to be measured, the surface of the working electrode is roughened so that the working electrode has a microstructure, such as a conical microstructure.

[0010] In order to improve the sensor response signal and increase the effective contact area between the semi-solid electrolyte layer and the working electrode, a concave-convex structure is provided at the interface between the semi-solid electrolyte layer and the working electrode.

[0011] In order to ensure the air permeability of the breathable substrate structure, so that the counter electrode is fully in contact with the air and a reduction reaction occurs, the breathable substrate structure can be a substrate formed with a microporous structure, and the micropores in the microporous structure are through holes with a pore size of 20-60 μm; the breathable substrate structure can also include a non-porous substrate and a waterproof and breathable layer arranged between the non-porous substrate and the counter electrode, and the waterproof and breathable material is polytetrafluoroethylene (PTFE).

[0012] The working principle of the MEMS electrochemical gas sensor is that the gas to be measured undergoes an oxidation reaction when it reaches the surface of the working electrode, and the generated positive ions are transmitted to the surface of the counter electrode through the semi-solid electrolyte film; since the substrate structure has good air permeability, oxygen in the air can reach the surface of the counter electrode and combine with positive ions and electrons to produce a reduction reaction. The electrochemical reaction causes a current to flow through the external circuit, and the concentration of the gas to be measured is obtained by measuring the voltage of the external load.

[0013] The present invention also provides a method for processing the above-mentioned MEMS electrochemical gas sensor, which comprises the steps of: processing a gas-permeable substrate structure, processing a counter electrode, processing a semi-solid electrolyte layer, and processing a working electrode; wherein the step of processing the semi-solid electrolyte layer comprises: first spraying or spin coating a semi-solid electrolyte solution on the counter electrode by a spraying or spin coating process, and then performing a drying and curing treatment, thereby forming a semi-solid electrolyte layer on the counter electrode, wherein the process parameters of the drying and curing treatment are: a drying temperature of 90-150°C and a drying time of 30-60 min.

[0014] Furthermore, the mass percentage concentration of the semi-solid electrolyte layer solution is preferably 5%-10%.

[0015] In order to increase the effective contact area between the semi-solid electrolyte layer and the counter electrode and improve the sensor response signal, the step of processing the semi-solid electrolyte layer may include: first spraying or spin coating the semi-solid electrolyte solution on the counter electrode by a spraying or spin coating process, then performing the drying and curing process, and then using a nanoimprinting or etching process to process a concave-convex structure on the semi-solid electrolyte layer; or first using a covering mask to perform a concave-convex patterning spraying process on the counter electrode, and then performing the drying and curing process, so as to process a concave-convex structure on the semi-solid electrolyte layer.

[0016] The step of processing the breathable substrate structure may include: processing a microporous structure on the non-porous substrate by laser drilling, dry etching or wet etching to form the breathable substrate structure. In addition, the step of processing the breathable substrate structure may also include: first using a spray coating process or a spin coating process, and then combining a drying and curing process to form a waterproof breathable layer on the non-porous substrate; or using a sputtering process to form a waterproof breathable layer on the non-porous substrate.

[0017] The step of processing the working electrode comprises: using a sputtering or evaporation or spraying or spin coating process, combined with a surface roughening process, to process a layer of working electrode with a microstructure on the semi-solid electrolyte layer.

[0018] Therefore, the MEMS electrochemical gas sensor provided by the present invention can control the thickness of the semi-solid electrolyte layer to 1-30 μm in combination with the MEMS process, which can not only make the sensor size up to 1 mm, but also because the semi-solid electrolyte layer is relatively thin, the internal resistance is low, and ion transmission is easy, so that the high sensor response is fast and the output signal is high enough; in this way, the MEMS electrochemical gas sensor provided by the present invention can not only be miniaturized and work with zero power consumption, but also have a good response signal, so that its load resistance is in the kilo-ohm level and the output current reaches the μA level; it can be used to monitor reducing gases such as carbon monoxide (CO), ethanol, and formaldehyde. The entire sensor structure and process are simple, and there is no need to prepare complex slurry. It can be mass-produced and integrated packaged, which significantly reduces the cost of each sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A cross-sectional view of the structure of a MEMS electrochemical gas sensor provided in Example 1 of the present invention; Figure 2 A top view of the MEMS electrochemical gas sensor structure provided in Example 1 of the present invention; Figure 3 This is a performance test result diagram of the MEMS electrochemical gas sensor provided in Example 1 of the present invention, wherein 100 ppm CO was introduced six times in succession; Figure 4 A cross-sectional view of the structure of a MEMS electrochemical gas sensor provided in Example 2 of the present invention; Figure 5 A cross-sectional view of the structure of a MEMS electrochemical gas sensor provided in Example 3 of the present invention; Figure 6 This is a cross-sectional view of the MEMS electrochemical gas sensor structure provided in Example 4 of the present invention.

[0020] Among them, the component symbols in each figure are: 101, 201, hard substrate, 102, 202, 302, 402, working electrode, 103, 203, 303, 403, semi-solid electrolyte layer, 104, 204, 304, 404, counter electrode, 105, 205, 305, 405, pad, 107, 407, micropore, 206, waterproof and breathable layer, 301, ceramic substrate, 306, reference electrode, 401, flexible substrate. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described in detail below through specific implementation methods.

[0022] The terms used in the present invention are all commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field unless otherwise specified.

[0023] The present invention is mainly based on semi-solid electrolyte materials such as Nafion solution, PVDF solution, PMMA solution, LLTO solution, etc., and uses spraying or spin coating, drying and curing to process the semi-solid electrolyte layer, and combines the MEMS process to design and prepare the MEMS electrochemical gas sensor. Not only can the size of the sensor structure be reduced to 1 mm, miniaturization and zero power consumption can be achieved, but also the sensor can have a good response signal, the load resistance is in the kilo-ohm level, and the output current reaches the μA level.

[0024] Specifically, an object of the present invention is to provide a MEMS electrochemical gas sensor, which is mainly composed of a gas permeable substrate structure, a counter electrode, a semi-solid electrolyte layer and a working electrode, wherein the counter electrode is arranged on the gas permeable substrate structure, and the counter electrode, the semi-solid electrolyte and the working electrode form a "sandwich" structure, wherein the semi-solid electrolyte layer is mainly a thin film structure formed by baking a semi-solid electrolyte solution. The semi-solid electrolyte solution is mainly an electrolyte composed of a solid polymer and a liquid plasticizer, and the semi-solid electrolyte layer formed by baking has high conductivity, high mechanical strength and good high temperature stability. The polymer molecules in the semi-solid electrolyte solution present a cross-linked spatial network structure, and the liquid plasticizer is filled in the pores of the structure; it includes but is not limited to Nafion solution, polyvinylidene fluoride (PVDF) solution, polymethyl methacrylate (PMMA) solution, lithium lanthanum titanium oxide (LLTO) solution, etc. The semi-solid electrolyte solution can be directly purchased from the market, or it can be obtained by diluting a commercially available product with an organic solvent. The thickness of the semi-solid electrolyte layer is preferably 1-30 μm.

[0025] In order to improve the sensor response signal and make the working electrode fully contact with the gas to be measured, the surface of the working electrode is roughened so that the working electrode has a microstructure, such as a conical microstructure.

[0026] In order to improve the sensor response signal and increase the effective contact area between the semi-solid electrolyte layer and the working electrode, a concave-convex structure is provided at the interface between the semi-solid electrolyte layer and the working electrode.

[0027] The materials of the working electrode and the counter electrode are platinum (Pt), gold (Au), Pt / C and other noble metals with catalytic effects and their mixtures, and the thickness is preferably 0.5-10 μm.

[0028] In order to ensure the air permeability of the air permeable substrate structure, so that the counter electrode is fully in contact with the air and a reduction reaction occurs, the air permeable substrate structure may be a substrate formed with a microporous structure, wherein the micropores in the microporous structure are through holes with a pore size of 20-60 μm; the air permeable substrate structure may also include a non-porous substrate and a waterproof air permeable layer disposed between the non-porous substrate and the counter electrode, wherein the waterproof air permeable material is polytetrafluoroethylene (PTFE). The air permeable substrate structure includes a silicon substrate, a glass substrate, a ceramic substrate or a flexible substrate, etc., wherein the substrate material used in the present invention is not limited to silicon, glass, ceramic, and a flexible polymer, and the flexible polymer may be polyimide (PI), polydimethylsiloxane (PDMS), etc.

[0029] Furthermore, the MEMS electrochemical gas sensor further comprises a plurality of pads disposed on the gas permeable substrate structure, and the counter electrode and the working electrode are respectively connected to the corresponding pads via wires, wherein the wires and pads are usually made of gold (Au).

[0030] Furthermore, the MEMS electrochemical gas sensor further includes a reference electrode disposed on the semi-solid electrolyte layer, and the reference electrode is spaced apart from the working electrode.

[0031] The working principle of the MEMS electrochemical gas sensor is that the gas to be measured undergoes an oxidation reaction when it reaches the surface of the working electrode, and the generated positive ions are transmitted to the surface of the counter electrode through the semi-solid electrolyte film; since the substrate structure has good air permeability, oxygen in the air can reach the surface of the counter electrode and combine with positive ions and electrons to produce a reduction reaction. The electrochemical reaction causes a current to flow through the external circuit, and the concentration of the gas to be measured is obtained by measuring the voltage of the external load.

[0032] Another object of the present invention is to provide a method for processing the above-mentioned MEMS electrochemical gas sensor, which comprises the steps of: processing a gas-permeable substrate structure, processing a counter electrode, processing a semi-solid electrolyte layer, and processing a working electrode; wherein the step of processing the semi-solid electrolyte layer comprises: first spraying or spin coating a semi-solid electrolyte solution on the counter electrode by a spraying or spin coating process, and then performing a drying and curing treatment to form a semi-solid electrolyte layer on the counter electrode, wherein the process parameters of the drying and curing treatment are: a drying temperature of 90-150°C and a drying time of 30-60 min.

[0033] The semi-solid electrolyte solution is mainly composed of a solid polymer and a liquid plasticizer. In the process of processing the semi-solid electrolyte layer, the baking and curing treatment is mainly to remove the organic solvent in the semi-solid electrolyte layer solution and reduce the internal resistance of the sensor; but if the baking temperature is too low or the drying time is too short, the solvent will not evaporate completely, the internal resistance will be large, and the zero point of the sensor will be high; if the baking temperature is too high or the drying time is too long, the ionic conductivity of the formed semi-solid electrolyte layer will decrease, thereby reducing the output signal. Therefore, the process parameters of the baking and curing treatment are: baking temperature 90-150℃, baking time 30-60 min.

[0034] Furthermore, the step of processing the semi-solid electrolyte layer includes: first spraying or spin coating the semi-solid electrolyte solution onto the counter electrode, and then performing the drying and curing treatment. Among them, the concentration of the semi-solid electrolyte layer solution should not be too high, otherwise there will be problems such as prolonged response time and sensor baseline offset; it should not be too low, otherwise it will cause the sensor sensitivity to decrease and the measurable range to narrow. Therefore, the mass percentage concentration of the semi-solid electrolyte layer solution is preferably 5%-10%. In the process of processing the semi-solid electrolyte layer, the thickness of the semi-solid electrolyte layer can be controlled by controlling the spraying amount or spin coating amount, and the thickness range is 1-30 μm.

[0035] In order to increase the effective contact area between the semi-solid electrolyte layer and the counter electrode and improve the sensor response signal, the step of processing the semi-solid electrolyte layer also includes: the step of processing the semi-solid electrolyte layer may include: first spraying or spin coating the semi-solid electrolyte solution on the counter electrode by a spraying or spin coating process, then performing the drying and curing process, and then using a nanoimprinting or etching process to process a concave-convex structure on the semi-solid electrolyte layer; or the step of processing the semi-solid electrolyte layer may also include: first performing a concave-convex patterning spraying process on the counter electrode by using a covering mask, and then performing the drying and curing process, so as to process a concave-convex structure on the semi-solid electrolyte layer.

[0036] The step of processing the breathable substrate structure includes: processing the non-porous substrate with breathable holes to process the breathable substrate structure. Specifically, this step may include: processing the microporous structure on the non-porous substrate by laser drilling, dry etching or wet etching to form the breathable substrate structure. In addition, the step of processing the breathable substrate structure may also include: first using a spray coating process or a spin coating process, and then combining a drying and curing process to form a waterproof breathable layer on the non-porous substrate; or using a sputtering process to form a waterproof breathable layer on the non-porous substrate.

[0037] The step of processing the counter electrode comprises: processing a layer of the counter electrode on the permeable substrate structure by sputtering, evaporation, spraying, spin coating or screen printing.

[0038] The step of processing the working electrode comprises: using a sputtering or evaporation or spraying or spin coating process, combined with a surface roughening process, to process a layer of working electrode with a microstructure on the semi-solid electrolyte layer.

[0039] The steps of processing the counter electrode and the steps of processing the working electrode both adopt existing technologies, and if necessary, the electrode can be patterned by photolithography, etching process or physical mask covering process. Specifically: the step of processing the counter electrode includes: using sputtering or evaporation or spraying or spin coating or screen printing process to process a layer of counter electrode on the permeable substrate. The step of processing the working electrode includes: firstly using sputtering or evaporation or spraying or spin coating process to process the working electrode film on the semi-solid electrolyte layer, and then using dry etching or wet etching to process the microstructure on the working electrode film, so as to form the working electrode.

[0040] The pad and the reference electrode can be processed by existing sputtering, evaporation, spraying or spin coating processes, and can be patterned by photolithography, etching or physical mask covering processes if necessary.

[0041] Furthermore, the preparation method further comprises the steps of cutting and dicing and die bonding and wire binding, wherein after the cutting and dicing steps, a single chip package such as plastic packaging, ceramic packaging, metal packaging, etc. can be used, or it can be integrated with an ASIC chip. Therefore, the technical solution provided by the present invention has the following advantages: (1) The semi-solid electrolyte layer of the MEMS electrochemical gas sensor provided by the present invention has a thickness of 1-30 μm, which is relatively thin, has low internal resistance, and is easy for ion transmission, so that the sensor has a fast response and a sufficiently high output signal; (2) The permeable substrate structure in the MEMS electrochemical gas sensor designed by the present invention achieves permeability by processing micropores on the substrate or processing other permeable layer structures; the surface of the working electrode is roughened, and / or a concave-convex structure is provided at the interface between the semi-solid electrolyte layer and the working electrode to increase the effective contact area, thereby improving the sensor response signal; therefore, although the volume of the MEMS electrochemical gas sensor provided by the present invention is greatly reduced, it still has a good response signal.

[0042] (3) The semi-solid electrolyte layer in the MEMS electrochemical gas sensor provided by the present invention forms a "sandwich" structure with the working electrode and the counter electrode. The working electrode contacts the gas to be measured to produce an oxidation reaction. The generated hydrogen ions and electrons reach the surface of the counter electrode through the relatively thin semi-solid electrolyte layer. A small amount of oxygen penetrates into the surface of the counter electrode through the air-permeable structure on the substrate and combines with the hydrogen ions and electrons to produce a reduction reaction, thereby realizing a spontaneous redox reaction and achieving zero power consumption of the sensor. The MEMS electrochemical gas sensor can be used to monitor reducing gases such as carbon monoxide, ethanol or formaldehyde.

[0043] (4) The semi-solid electrolyte in the MEMS electrochemical gas sensor can be processed by spraying or spin coating, drying and curing process, the counter electrode and working electrode can be processed by sputtering or evaporation or spraying or spin coating process, and each element in the sensor can be patterned by photolithography, etching process or physical mask covering process if necessary; therefore, the sensor can be batch processed by MEMS process instead of using the commonly used electrochemical assembly method, so as to achieve miniaturization and integration, so that the size of the sensor can be made to 1 mm, for example, if the sensor is square, the minimum side length can be made to 1 mm; if it is round, the minimum diameter can be made to 1 mm.

[0044] Example 1 See also Figure 1 and Figure 2 Embodiment 1 of the present invention provides a MEMS electrochemical gas sensor, which is mainly composed of a hard substrate 101 with micropores 107, a working electrode 102, a semi-solid electrolyte layer 103, a counter electrode 104 and two pads 105. The counter electrode 104 is arranged on the surface of the hard substrate 101 and covers the micropores 107 therein. In this embodiment, the micropores 107 are evenly distributed in the middle area of ​​the hard substrate 101, with a pore size of 50 μm, and the hard substrate 101 is a silicon substrate. The working electrode 102, the semi-solid electrolyte layer 103 and the counter electrode 104 form a "sandwich" structure. The interface between the semi-solid electrolyte layer 103 and the working electrode 102 is provided with a concave-convex structure. Specifically, the semi-solid electrolyte layer 103 is evenly provided with a plurality of grooves. The working electrode 102 includes a plurality of conical structures and concave structures alternately arranged. The concave structures are filled in the corresponding grooves on the solid electrolyte layer 103, so that the surface of the concave structures is flush with the surface of the solid electrolyte layer 103 around it, and the adjacent conical structures are connected by the concave structures. The pad 105 is arranged in an area without micropores on the substrate 101, and the working electrode 102 and the counter electrode 104 are connected to the corresponding pad 105 through a wire. In this embodiment, the working electrode 102 and the counter electrode 104 are made of Pt, and the wire and the pad 105 are made of gold.

[0045] This embodiment also provides a processing technology for the above-mentioned MEMS electrochemical gas sensor, and the specific process flow is as follows: (1) Processing a breathable substrate structure: a microporous structure is processed in the middle area of ​​the original silicon wafer by laser drilling process, and a plurality of micropores 107 evenly distributed in the middle area of ​​the hard substrate 101 are formed, wherein the micropores 107 are through holes, which facilitate air to reach the surface of the counter electrode 104, so that a small amount of oxygen therein undergoes a reduction reaction on the counter electrode 104; (2) Processing the counter electrode: a layer of Pt is processed on the microporous area of ​​the substrate 101 by sputtering process as the counter electrode 104, with a thickness of 2 μm; (3) Processing pads: Processing a layer of gold as a wire and pad 105 in the non-micropore area of ​​the hard substrate 101 by sputtering, photolithography and etching processes, with a thickness of 1 μm, and one of the wires is connected to the counter electrode; (4) Processing the semi-solid electrolyte layer: first spray a 5% Nafion solution onto the counter electrode 104, and then perform drying and curing treatment to form a Nafion film. Patterning treatment can be achieved by spraying with a physical mask to form a plurality of evenly distributed grooves on the surface of the Nafion film, thereby processing and forming the semi-solid electrolyte layer 103. The process parameters of the drying and curing treatment are shown in Table 1. (5) Processing the working electrode: first, a Pt film is formed on the surface of the semi-solid electrolyte layer 103 by a sputtering process, and the Pt film fills the grooves on the Nafion film; then, the Pt film is patterned by a photolithography and etching process to form a plurality of conical structures as the working electrode 102, with a thickness of 1 μm, and the working electrode is connected to another wire; (6) Cutting and dicing: Cut into multiple square sensors with a size of 1 mm × 1 mm × 0.3 mm. The cut sensor chips are packaged individually.

[0046] The following response performance test was performed on the MEMS electrochemical gas sensor samples 1-8 provided in this embodiment, and the results are shown in Table 1. The response performance test method is as follows: the sensor to be tested is connected in series with a 10 kΩ load resistor, 100 ppm carbon monoxide CO is introduced into the test gas, the voltage change across the load resistor is tested, the output current value is calculated, and the zero-point voltage of the sensor is recorded. The response curve of sample 3 after six consecutive response performance tests is shown in Table 1. Figure 3 shown.

[0047] Table 1 MEMS electrochemical gas sensor performance test

[0048] The concentrations of Nafion solutions in the table are: 5% is directly commercially available, 3% is obtained by diluting 5% with ethanol, and 8% and 10% are obtained by diluting 20% ​​commercially available with ethanol.

[0049] From the analysis of Table 1, we can see that: 1) During the processing of semi-solid electrolyte, the baking temperature should not be too high, otherwise the ionic conductivity of the semi-solid electrolyte layer will decrease, thereby reducing the output signal; the baking temperature should not be too low, otherwise the internal resistance will be large and the zero point of the sensor will be high; therefore, the baking temperature is preferably 90-150℃; 2) During the processing of semi-solid electrolyte, if the baking time is too long, the ionic conductivity of the semi-solid electrolyte layer will also decrease, and the output signal will be reduced; if the baking time is too short, the solvent will not evaporate completely, the internal resistance will be large, and the zero point of the sensor will be high; therefore, the baking time is preferably 30-60 min; 3) The concentration of Nafion solution should not be too high, otherwise it will cause problems such as prolonged response time and sensor baseline offset; it should not be too low, otherwise it will cause reduced sensor sensitivity and narrow measurable range; therefore, the mass percentage concentration of Nafion solution is preferably 5%-10%.

[0050] It can be seen from Table 1 that sample 3 has the best response performance. Figure 3 From the response curve of the sample 3 shown in FIG. 3 after six consecutive responses to the response performance test, it can be seen that the MEMS electrochemical gas sensor made from the sample 3 has good stability in its response signal because the presence of micropores can limit the air intake amount and air intake rate.

[0051] Example 2 See also Figure 4 , this embodiment provides a MEMS electrochemical gas sensor, which is mainly composed of a non-porous hard substrate 201, a working electrode 202, a semi-solid electrolyte layer 203, a counter electrode 204, two pads 205, and a waterproof breathable layer 206, wherein the waterproof breathable layer 206 is arranged in the middle of the hard substrate 201 to form a breathable substrate structure. The counter electrode 204 is arranged on the surface of the waterproof breathable layer 206. In this embodiment, the material of the waterproof breathable layer 206 is polytetrafluoroethylene, the semi-solid electrolyte layer 203 is a PMMA layer, and the hard substrate 201 is a glass substrate. The working electrode 202, the semi-solid electrolyte layer 203 and the counter electrode 204 form a "sandwich" structure. The working electrode 202 is a continuous membrane structure with a conical microstructure with a roughened surface. The pad 205 is arranged on the waterproof breathable layer 206, and the working electrode 202 and the counter electrode 204 are connected to the corresponding pad 205 through a wire.

[0052] This embodiment also provides a processing technology for the above-mentioned MEMS electrochemical gas sensor, and the specific process flow is as follows: (1) Processing a breathable substrate structure: using non-porous glass as a hard substrate 201, and forming a polytetrafluoroethylene layer on the hard substrate 201 by a spraying process as a waterproof breathable layer 206; (2) Processing the counter electrode: a layer of Pt as the counter electrode 204 is processed in the middle area of ​​the waterproof and breathable layer 206 by screen printing technology, with a thickness of 5 μm; (3) Processing pads: Processing a layer of gold as a wire and pad 205 on the edge of the waterproof and breathable layer 206 by sputtering, photolithography and etching processes, with a thickness of 1 μm, and one of the wires is connected to the counter electrode; (4) Processing the semi-solid electrolyte layer: first spray a 5% PMMA solution onto the counter electrode 104, then dry and cure it at 120° C. for 30 min to form a PMMA film, and process it to form the semi-solid electrolyte layer 203 with a thickness of 15 μm; (5) Processing the working electrode: a Pt / C film is formed on the surface of the semi-solid electrolyte layer 203 by using a physical mask covering spraying process; the Pt / C film is then roughened by using an etching process to serve as the working electrode 202 with a thickness of 5 μm, and the working electrode 202 is connected to another wire; (6) Cutting and dicing: Cutting into multiple square sensors with a size of 1 mm × 1 mm × 0.5 mm; the cut sensor chips are bonded with die bonding wires.

[0053] Example 3 like Figure 5 As shown, this embodiment provides a MEMS electrochemical gas sensor, which is mainly composed of a loose and porous ceramic substrate 301, a working electrode 302, a semi-solid electrolyte 303, a counter electrode 304, a pad 305, and a reference electrode 306. Among them, the working electrode 302, the semi-solid electrolyte layer 303 and the counter electrode 304 form a "sandwich" structure. The working electrode 302 and the reference electrode 306 are arranged on the semi-solid electrolyte layer 303 at intervals, and the working electrode 302 is a continuous conical structure. The pad 305 is arranged on the ceramic substrate 301, and the working electrode 302, the counter electrode 304 and the reference electrode 306 are connected to the corresponding pad 305 through a wire. In this embodiment, the material of the working electrode 302 and the counter electrode 304 is Pt, the material of the reference electrode is Ag / AgCl, and the material of the wire and the pad 305 is gold.

[0054] This embodiment also provides a processing technology for the above-mentioned MEMS electrochemical gas sensor, and the specific process flow is as follows: (1) Processing a breathable substrate structure: A loose and porous ceramic substrate 301 with a porosity of 25% is used as the breathable substrate structure; (2) Processing the counter electrode: a layer of Pt as the counter electrode 304 with a thickness of 0.5 μm is processed in the middle area of ​​the ceramic substrate 301 by a sputtering process; (3) Processing pads: Processing a layer of gold on the edge of the ceramic substrate 301 by sputtering, photolithography and etching processes to serve as three wires and pads 305, with a thickness of 0.5 μm, and one of the wires is connected to the counter electrode; (4) Processing the semi-solid electrolyte layer: first spray a 5% Nafion solution onto the counter electrode 304, then dry and cure it at 120°C for 60 min to form a Nafion film, and process it to form the semi-solid electrolyte layer 303 with a thickness of 13 μm; (5) Processing the working electrode and the reference electrode: first, a layer of Pt thin film is formed on the surface of the semi-solid electrolyte layer 303 by a sputtering process; then, the Pt thin film is patterned by a photolithography and etching process to form a working electrode 302 with a conical structure on the semi-solid electrolyte layer 303, and then a reference electrode 306 is prepared by a physical mask covering sputtering method, with a thickness of 1 μm, and the working electrode and the reference electrode are connected to the other two wires; (6) Cutting and dicing: Cutting into multiple square sensors with a size of 1 mm × 1 mm × 0.3 mm; integrating the cut sensor chip and ASIC chip into a package.

[0055] Example 4 This embodiment provides a MEMS electrochemical gas sensor, such as Figure 6 As shown, it mainly consists of a flexible substrate 401 with micropores 407, a working electrode 402, a semi-solid electrolyte 403, a counter electrode 404, and a pad 405; the structure is basically the same as the MEMS electrochemical gas sensor provided in Example 1, and the main difference is that: in this embodiment, a flexible substrate polyimide (PI) is used instead of a hard substrate, no concave-convex structure is set at the interface between the working electrode 402 and the semi-solid electrolyte 403, a conical microstructure is processed on the surface of the working electrode 402, and the semi-solid electrolyte 403 is a PVDF layer. The other structures are the same as the structure of the sensor provided in Example 1.

[0056] This embodiment also provides a processing technology for the above-mentioned MEMS electrochemical gas sensor, and the specific process flow is as follows: (1) Processing a breathable substrate structure: Processing a microporous structure on the middle area of ​​the flexible PI film by laser punching process, forming a plurality of uniformly distributed micropores 407 in the middle area of ​​the PI film to serve as a flexible breathable substrate structure; (2) Processing the counter electrode: a layer of Pt as the counter electrode 404 with a thickness of 2 μm is processed on the microporous area of ​​the flexible substrate 401 by sputtering, photolithography and etching processes; (3) Processing pads: Processing a layer of gold as a conductor and pad 405 on the flexible substrate 401 by sputtering, photolithography and etching processes, with a thickness of 1 μm; (4) Processing the semi-solid electrolyte layer: first spray a PVDF solution with a concentration of 8% onto the counter electrode 104, then dry and cure it at 120° C. for 45 min to form a PVDF film, and process it to form the semi-solid electrolyte layer 203 with a thickness of 15 μm; (5) Processing the working electrode: first, a layer of Pt film is formed on the surface of the semi-solid electrolyte layer 203 by a sputtering process; then, the Pt film is patterned by a photolithography and etching process to form a conical microstructure as the working electrode 402 with a thickness of 1 μm, and the working electrode 402 is connected to another wire; (6) Cutting and dicing: Cutting into multiple square sensors with a size of 1 mm × 1 mm × 0.1 mm. The cut sensor chips can be bonded and packaged separately, or integrated with ASIC chips.

[0057] In summary, the MEMS electrochemical gas sensor provided in the embodiment of the present invention is a zero-power, miniaturized sensor made mainly by controlling the processing technology of the semi-solid electrolyte layer and combining the MEMS process. The size of the sensor can be 1mm, the load resistance is in the kilo-ohm level, and the output current is in the μA level. Its response performance is equivalent to the output signal of the traditional cm-level large-size electrochemical sensor, which is much higher than the nA level disclosed by the existing MEMS electrochemical solid electrolyte gas sensor; therefore, the MEMS electrochemical gas sensor provided in the embodiment of the present invention can not only be miniaturized and zero-power, but also have a good response signal; it can be used to monitor reducing gases such as CO, ethanol, and formaldehyde. The entire sensor structure and process are simple, and there is no need to prepare complex slurry. It can be mass-produced and integrated packaged, which significantly reduces the cost of each sensor.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.

Claims

1. A MEMS electrochemical gas sensor, characterized in that: It is mainly composed of a breathable substrate structure, a counter electrode, a semi-solid electrolyte layer and a working electrode, and the counter electrode, the semi-solid electrolyte and the working electrode form a "sandwich" structure, wherein the semi-solid electrolyte layer is mainly a thin film structure formed by baking a semi-solid electrolyte solution, and the semi-solid electrolyte solution is mainly composed of a solid polymer and a liquid plasticizer.

2. The MEMS electrochemical gas sensor according to claim 1, characterized in that: The semi-solid electrolyte solution includes Nafion solution, polyvinylidene fluoride solution, polymethyl methacrylate solution or lithium lanthanum titanium oxide solution.

3. The MEMS electrochemical gas sensor according to claim 1, characterized in that: The working electrode has a microstructure.

4. The MEMS electrochemical gas sensor according to claim 3, characterized in that: A concave-convex structure is arranged at the interface between the semi-solid electrolyte layer and the working electrode.

5. The MEMS electrochemical gas sensor according to any one of claims 1 to 4, characterized in that: The air-permeable substrate structure is a substrate formed with a microporous structure, and the micropores in the microporous structure are through holes with a pore diameter of 20-60 μm.

6. The MEMS electrochemical gas sensor according to any one of claims 1 to 4, characterized in that: The air-permeable substrate structure includes a non-porous substrate and a waterproof air-permeable layer, and the waterproof air-permeable layer is arranged between the non-porous substrate and the counter electrode.

7. The MEMS electrochemical gas sensor according to claim 1, characterized in that: The gas-permeable substrate structure includes a silicon substrate, a glass substrate, a ceramic substrate or a flexible substrate.

8. The MEMS electrochemical gas sensor according to claim 1, characterized in that: It also includes a reference electrode disposed on the semi-solid electrolyte layer, wherein the reference electrode is spaced apart from the working electrode.

9. A method for processing the MEMS electrochemical gas sensor according to claim 1, comprising the steps of: processing a gas permeable substrate structure, processing a counter electrode, processing a semi-solid electrolyte layer, and processing a working electrode; in, The step of processing the semi-solid electrolyte layer includes: first spraying or spin coating the semi-solid electrolyte solution on the counter electrode by a spraying or spin coating process, and then performing a drying and curing treatment to form a semi-solid electrolyte layer, and the process parameters of the drying and curing treatment are: drying temperature 90-150°C, drying time 30-60 min.

10. The processing method according to claim 9, characterized in that: The mass percentage concentration of the semi-solid electrolyte layer solution is preferably 5%-10%.

11. The processing method according to claim 9 or 10, characterized in that: The step of processing the semi-solid electrolyte layer comprises: firstly spraying or spin coating the semi-solid electrolyte solution on the counter electrode by a spray coating or spin coating process, then performing the drying and curing process, and then processing a concave-convex structure on the semi-solid electrolyte layer by a nano-imprinting or etching process; Alternatively, a concave-convex patterning spraying process is first performed on the counter electrode using a covering mask, and then the drying and curing process is performed.

12. The processing method according to claim 9 or 10, characterized in that: The step of processing the air-permeable substrate structure includes: processing a microporous structure on the non-porous substrate by using a laser drilling method, a dry etching method, or a wet etching method to form the air-permeable substrate structure.

13. The processing method according to claim 9 or 10, characterized in that: The steps of processing the breathable substrate structure include: first using a spraying process or a spin coating process, and then combining a drying and curing process to form a waterproof breathable layer on the non-porous substrate; or using a sputtering process to form a waterproof breathable layer on the non-porous substrate.

14. The processing method according to claim 9 or 10, characterized in that: The step of processing the working electrode comprises: using a sputtering or evaporation or spraying or spin coating process, combined with a surface roughening process, to process a layer of working electrode with a microstructure on the semi-solid electrolyte layer.

Citation Information

Patent Citations

  • Ultrathin all-solid-state formaldehyde electrochemical gas sensor

    CN113588738A

  • Membrane electrode of gas sensor and preparation method and application thereof

    CN117110393A

  • Preparation method of PCB-based electrochemical semi-solid gas sensor

    CN117269278A

  • Hybrid potential type gas sensor based on MEMS technology and preparation method thereof

    CN117805199A

Cited By

  • Solid electrolyte for ammonia gas detection, electrochemical luminescence sensor, preparation method and detection method

    CN121253631A

  • MEMS amperometric gas sensor

    CN121431636A

  • A suspended thin-film MEMS electrochemical sensor and its preparation method and application

    CN122754277A